If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -5x + 3 = 5 + -2x + 7 + -10x Reorder the terms: 2 + 3 + -5x = 5 + -2x + 7 + -10x Combine like terms: 2 + 3 = 5 5 + -5x = 5 + -2x + 7 + -10x Reorder the terms: 5 + -5x = 5 + 7 + -2x + -10x Combine like terms: 5 + 7 = 12 5 + -5x = 12 + -2x + -10x Combine like terms: -2x + -10x = -12x 5 + -5x = 12 + -12x Solving 5 + -5x = 12 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 5 + -5x + 12x = 12 + -12x + 12x Combine like terms: -5x + 12x = 7x 5 + 7x = 12 + -12x + 12x Combine like terms: -12x + 12x = 0 5 + 7x = 12 + 0 5 + 7x = 12 Add '-5' to each side of the equation. 5 + -5 + 7x = 12 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = 12 + -5 7x = 12 + -5 Combine like terms: 12 + -5 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 4x+9=-7x+31 | | 7x+11=3x+59 | | 3-a=4a+13 | | -5x+6x+15-12x= | | -4.4s=-5.5s-4.3 | | 2+(-21)= | | -3x+25+x+21=3 | | -23-3y+31= | | 15x-7=14x+12 | | T-7=30 | | -3y-1=-2y-8 | | 3y-23-6y+31= | | Y+5=-1 | | 2s+3=15 | | -2(7-5m+n)= | | X-(-9)=6 | | x+y+5=60 | | (3x-2)2=13 | | logx+6-logx-4=1 | | 12y-6=139 | | 2(2x-4)=18 | | 7-(4x-5)=2-5x | | 8(3X-4)=4X+8 | | 22=3p-4 | | x-(x+10)=12 | | 6=2y+9 | | (x+3)7= | | 1/z=2/9 | | -3=12+x | | 6y-6=6x-29 | | (i)(8i)(-4+7i)=0 | | 5e(3x-1)=7 |